Extracellular Vesicle miR-200c Enhances Gefitinib Sensitivity in Heterogeneous EGFR-Mutant NSCLC - Chien-Chung Lin; Chin-You Wu; Joseph Ta-Chien Tseng; Chun-Hua Hung; Shang-Yin Wu; Yu-Ting Huang; Wei-Yuan Chang; Po-Lan Su; Wu-Chou Su (Biomedicines, 2021)
Intratumoral heterogeneity in epidermal growth factor receptor (EGFR)-mutant mutant non-small-cell lung cancer (NSCLC) explains the mixed responses to EGFR-tyrosine kinase inhibitors (TKIs). However, some studies showed tumors with low abundances of EGFR mutation still respond to EGFR-TKI, and the mechanism remained undetermined. Extracellular vesicles (EVs) can transmit antiapoptotic signals between drug-resistant and drug-sensitive cells. Herein, we profiled EVs from EGFR-mutant cells to identify a novel mechanism explaining why heterogenous EGFR-mutant NSCLC patients still respond to EGFR-TKIs. We first demonstrated that the EVs from EGFR-mutant changes the wild-type cells’ sensitivity to gefitinib by adding EV directly or coculturing EGFR wild-type (CL1-5) cells and EGFR-mutant (PC9) cells. In animal studies, only the combined treatment of PC9 EV and gefitinib delayed the tumor growth of CL1-5 cells. MicroRNA analysis comparing EV miRNAs from PC9 cells to those from CL1-5 cells showed that mir200 family members are most abundant in PC9 EVs. Furthermore, mir200a and mir200c were found upregulated in plasma EVs from good responders to EGFR-TKIs. Finally, the transfection of CL1-5 cells with miR200c inactivates downstream signaling pathways of EGFR, the EMT pathway, and enhances gefitinib sensitivity. Overall, our results suggest that in heterogeneous EGFR-mutant NSCLC, tumor cells transmit EV miRNAs that may affect sensitivity to EGFR-TKIs and provide potential prognostic biomarkers for EGFR-mutant NSCLC.